Comparative evaluations on the canal-centering ability of novel heat-treated retreatment file system using nano-computed tomography - Sruthi Sairaman; Pradeep Solete; Ganesh Jeevanandan; Prabhadevi C Maganur; Feras Majed Masha; Satish Vishwanathaiah (Wolters Kluwer Medknow Publications, 2024)
Introduction: The main goal of instrumentation during retreatment is to maintain the original curvature of the canal during retrieval of gutta-percha. The present study evaluates the canal-centering ability of two different retreatment file systems. Materials and Methods: Forty extracted single-rooted teeth were decoronated and obturated at the standardized root length of 16 mm. Samples were divided into two groups of each 20 single root teeth and they were instrumented using Solite RS3 Retreatment and ProTaper Retreatment files, respectively. Both pre- and postoperative nano-computed tomography scans were taken, and three-dimensional reconstruction was done for analysis. Sections of both the pre- and postoperative samples were taken at 7 mm, 5 mm, and 3 mm from the apex to calculate the canal-centering ratio. Independent t-test was used for statistical analysis between the two groups. Results: Solite RS3 retreatment files showed a significant difference at the 3 levels (P < 0.000) compared to ProTaper retreatment files. Conclusion: From the above results, we can conclude that Solite RS3 caused minimal canal transportation and produced a relatively centered preparation in comparison to the ProTaper Retreatment system.